2011
DOI: 10.1007/s11224-011-9744-9
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical investigation on the structures and stabilities of C60X18 and C70X10 (X = H, F, Cl, and Br)

Abstract: A density functional theory study was performed on fullerene derivatives C 60 X 18 and C 70 X 10 (X = H, F, Cl, and Br). The calculated results show that the lowest energy isomers are IPR-satisfying for C 60 X 18 (X = H, F, Cl, and Br). It is found that the addition patterns of X (X = Cl and Br) are different from those of X (X = H and F) for C 60 , demonstrating that the stability of fullerene derivatives is partly attributed to the steric repulsion and electronegativity of added atoms. However, the lowest en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Our systematical computations on C 60 X 18 , C 70 X 10 , and C 80 X 12 demonstrated that the addition patterns of chloride and bromide fullerenes are usually different from those of hydride and fluoride fullerenes. [54,55] Strain relief and pstabilization or aromaticity are dominating factors that control the stability of the hydrogenated and fluoride fullerenes. However, for chloride and bromide fullerenes, the exohedral atoms are usually in 1,4-addition instead of 1,2-addition to minimize the repulsion.…”
Section: Geometrical Rulesmentioning
confidence: 99%
“…Our systematical computations on C 60 X 18 , C 70 X 10 , and C 80 X 12 demonstrated that the addition patterns of chloride and bromide fullerenes are usually different from those of hydride and fluoride fullerenes. [54,55] Strain relief and pstabilization or aromaticity are dominating factors that control the stability of the hydrogenated and fluoride fullerenes. However, for chloride and bromide fullerenes, the exohedral atoms are usually in 1,4-addition instead of 1,2-addition to minimize the repulsion.…”
Section: Geometrical Rulesmentioning
confidence: 99%